High-temperature-resistant asphalt mixture and preparation method thereof
By grafting maleic anhydride and diatomaceous earth in the asphalt mixture, the problem of the asphalt mixture being prone to deformation under high temperature conditions is solved, higher high temperature resistance and stability are achieved, and the service life of the asphalt pavement is extended.
Patent Information
- Application Number
- CN202411566811.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-11
AI Technical Summary
Existing asphalt mixtures are prone to rheology and deformation under high temperature conditions, resulting in road depression, ruts and other diseases, reducing road durability and service life.
High-temperature resistant asphalt is prepared by grafting maleic anhydride with homemade composite filler and co-modifying asphalt with diatomaceous earth, and adding ore powder, gravel and other materials to prepare high-temperature resistant asphalt mixture.
It significantly improves the high temperature resistance of the asphalt mixture, enhances its stability and binding force, and extends the service life of the asphalt pavement.
Smart Images

Figure BDA0005119463980000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt mixtures, in particular to a high temperature resistant asphalt mixture and a preparation method thereof. Background Art
[0002] Asphalt mixture is mainly composed of asphalt, coarse aggregate, fine aggregate, mineral powder, and some also contain polymers and wood cellulose. Due to the strong adhesion between asphalt and aggregate, it provides excellent stability and improved mechanical properties, so it is widely used in the manufacture of flexible pavements.
[0003] However, huge traffic loads are repeatedly applied to the road surface, causing road surface damage, and under the influence of high temperatures in summer, the damage is greatly aggravated, which will cause serious defects in flexible pavements, such as asphalt drainage, fatigue cracks and permanent deformation. As the highway is exposed to the sun for a long time, the asphalt pavement absorbs heat in summer and the temperature rises sharply, up to 70°C. Asphalt, as a typical viscoelastic material, is very prone to rheological deformation under high temperature conditions. If a vehicle passes through the asphalt pavement at this time, the pavement is very likely to produce deformations that are difficult to recover, and dents, rutting and other diseases will occur. High temperature diseases not only destroy the flatness of the road surface and affect the comfort of the driver during driving, but also reduce the durability of the road. The rutting depressions will accumulate rainwater, and the water will enter the pavement structure, further damaging the road, causing the asphalt pavement to have pitting, potholes, cracks, mud pumping and other diseases, reducing the service life of the asphalt pavement. Therefore, studying how to improve the high temperature resistance of asphalt mixtures is of great significance for improving road quality and reducing maintenance costs. Summary of the invention
[0004] The object of the present invention is to provide a high temperature resistant asphalt mixture and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high temperature resistant asphalt mixture, wherein the asphalt mixture is prepared by grafting maleic anhydride with a homemade composite filler, adding diatomaceous earth and asphalt, mineral powder and crushed stone as raw materials.
[0006] Furthermore, the self-made composite filler is prepared by grafting sodium lignin sulfonate and chitosan onto basalt fiber, absorbing nano-metal particles, and then adding them into nitrile rubber.
[0007] Furthermore, the basalt fiber is activated basalt fiber treated with glacial acetic acid.
[0008] Furthermore, a method for preparing a high temperature resistant asphalt mixture comprises the following preparation steps:
[0009] (1) adding basalt fiber to glacial acetic acid solution with a solid-liquid ratio of 1:5, and then stirring the solution with a magnetic stirrer for 2 hours at a stirring speed of 120 / rpm; after the stirring, rinsing and filtering with deionized water, and circulating twice to clean the basalt fiber; placing the cleaned basalt fiber in an oven for drying, setting the temperature to 50°C for 8 hours, and obtaining activated basalt fiber after drying;
[0010] (2) Add 12-20 parts of deionized water to 1 part of chitosan, stir at 120 rpm for 10 min, then add 0.04-0.06 parts of organic acid and 0.1-0.5 parts of ethanol, continue to stir for 20 min, then add 0.5-1.5 parts of sodium lignin sulfonate and 5-8 parts of activated basalt fiber, stir at 80°C for 2 h, stir at 250 rpm, filter the filtrate after the reaction is completed, wash twice with deionized water; then The filtered material after washing is then mixed with deionized water 10 times its volume, and nano copper particles are added, the mass ratio of nano copper particles to the filtered material is 0.2-0.5:4, and then the mixture is mixed and stirred at a speed of 120 rpm for 30 minutes at a temperature of 60°C; after the stirring is completed, the filtered material is filtered and washed twice with deionized water to remove the unattached nano copper particles, and then placed in a drying oven at a temperature of 60°C for 5 hours, and then sent to an electron beam irradiation device for irradiation reaction for 10-15 minutes to obtain a composite filler;
[0011] (3) The rheometer is preheated to 150° C., and then a certain amount of maleic anhydride, dibenzoyl peroxide and composite filler are weighed in proportion, mixed, stirred at a speed of 60 rpm for 5 minutes, added to the cavity of the rheometer, and blended for 10 minutes at a temperature of 150° C. and a rotation speed of 60 rpm; after the blending is completed and cooled to room temperature, the blended product is crushed into fine particles with a particle size of 3-5 mm, and then ultrasonicated in anhydrous ethanol for 30 minutes at an ultrasonic power of 40 kHz to remove unreacted maleic anhydride to obtain a grafted maleic anhydride composite filler. The material is prepared by heating the base asphalt in an oven at 155°C, and then rapidly heating it to 180°C, mixing 14 parts of the base asphalt with 5-9 parts of grafted maleic anhydride composite filler and 2 parts of diatomaceous earth, and stirring them with a high-speed mixer at 1000rpm for 30min, and then adding 1-1.5 parts of 3mm crushed stone, 0.5-1 part of 1mm crushed stone, 1-2 parts of ore powder, and 2.6 parts of lignin fiber, and mixing and homogenizing for 30min at a speed of 560rpm and a temperature of 40-60°C. After stirring, a high temperature resistant asphalt mixture is obtained.
[0012] Furthermore, in step (1), the diameter of the basalt fiber is 3 mm.
[0013] Furthermore, the concentration of the glacial acetic acid solution in step (1) is 1 mol / L.
[0014] Furthermore, in step (2), the organic acid is acetic acid.
[0015] Furthermore, the irradiation energy in step (2) is 0.7 MeV.
[0016] Furthermore, in step (3), the mass ratio of maleic anhydride, dibenzoyl peroxide and composite filler is 0.02-0.04:5:2.
[0017] Furthermore, in step (3), the ore is divided into quicklime powder.
[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0019] The invention adopts self-made composite filler grafted with maleic anhydride, adds diatomaceous earth and asphalt, mineral powder and crushed stone as raw materials to prepare asphalt mixture, so as to achieve the effect of high temperature resistance.
[0020] First, sodium lignin sulfonate and chitosan are grafted onto basalt fibers, and after adsorbing nano-metal particles, they are added into nitrile rubber to make composite fillers; the hydroxyl groups on the surface of sodium lignin sulfonate, the amino and hydroxyl groups on the surface of chitosan, and the active groups on the surface of activated basalt fibers react and chemically combine with each other. The basalt fibers grafted with sodium lignin sulfonate have carbon chains and benzene rings on their surfaces, which greatly improve their dispersibility in rubber and strengthen the interfacial force of the basalt fibers as a hard skeleton to support the rubber to form a three-dimensional structure, so that the combination effect of the two is achieved. Good improvement, thereby comprehensively improving the stability of the composite filler; using the hydroxyl group at the ortho position of the free amino group of chitosan, which has the function of chelating divalent metal ions, the nano-metal copper particles are adsorbed on the basalt fiber through chelation to form a metal chelate; the nano-metal chelate has a significant effect on inhibiting the cross-linking reaction of the rubber molecular chain caused by free radicals, improving the stability of the rubber's resistance to heat and oxygen aging, and at the same time, because it is attached to the basalt fiber, it is evenly distributed in the composite filler, further improving the high temperature resistance of the composite filler, thereby optimizing the high temperature resistance of the asphalt mixture;
[0021] Secondly, maleic anhydride is grafted onto the composite filler through free radical polymerization reaction, and the asphalt is modified synergistically with diatomaceous earth to prepare an asphalt mixture; the addition of diatomaceous earth can undergo a cross-linking reaction with the asphalt to form a stable network structure, which combines with the composite filler to form a stable blend; on this basis, the grafted maleic anhydride not only reduces the problem of excessive viscosity caused by the cross-linking structure, but also further improves the combination effect of the composite filler with other substances in the asphalt mixture due to functional modification due to the introduction of its polar groups, so as to achieve higher stability. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a high temperature resistant asphalt mixture prepared in the following examples are as follows:
[0024] Marshall stability: The asphalt mixtures prepared in the examples and comparative examples were respectively taken as test objects, and standard Marshall specimens of 101.6±0.2mm×63.5±1.3mm were prepared by standard compaction method, and their Marshall stability was tested respectively. The specific test steps were based on T0709-2011 "Asphalt Mixture Marshall Stability Test" in JTG E20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".
[0025] High temperature stability: The asphalt mixtures prepared in the embodiment and the comparative example were respectively taken as test objects. The asphalt mixture samples were subjected to a rutting test according to the prescribed method (T0719), and the average value of three experiments was taken.
[0026] Example 1
[0027] (1) adding basalt fiber with a diameter of 3 mm into a glacial acetic acid solution with a concentration of 1 mol / L, with a solid-liquid ratio of 1:5, and then stirring the solution with a magnetic stirrer for 2 hours at a stirring speed of 120 / rpm; after the stirring, rinsing and filtering with deionized water, and the cycle is repeated twice to clean the basalt fiber; placing the cleaned basalt fiber in an oven for drying, setting the temperature to 50°C, and drying for 8 hours, and obtaining activated basalt fiber after drying;
[0028] (2) Add 12 parts of deionized water to 1 part of chitosan, stir at 120 rpm for 10 min, then add 0.04 parts of acetic acid and 0.1 parts of ethanol, continue to stir for 20 min, then add 0.5 parts of sodium lignin sulfonate and 5 parts of activated basalt fiber, stir and react at 80°C for 2 h, the stirring speed is 250 rpm, after the reaction is completed, filter and take the filtrate, wash it twice with deionized water; then mix the washed filtrate with 10 times its volume of deionized water, add nano copper particles, the mass ratio of nano copper to filtrate is 0.2:4, then mix and stir at 120 rpm for 30 min, the temperature is 60°C; after the stirring is completed, filter and take the filtrate, wash it twice with deionized water to wash away the unattached nano copper particles, then place it in a drying oven at a temperature of 60°C for 5 h, and send it to an electron beam irradiation device, react for 10 min at an irradiation energy of 0.7 MeV to obtain a composite filler;
[0029] (3) The rheometer was preheated to 150°C, and then maleic anhydride, dibenzoyl peroxide and composite filler were weighed in a mass ratio of 0.02:5:2. The maleic anhydride, dibenzoyl peroxide and composite filler were mixed, stirred at 60 rpm for 5 minutes, and then added to the cavity of the rheometer. The mixture was blended at 150°C and 60 rpm for 10 minutes. After the blending was completed and cooled to room temperature, the blended product was crushed into fine particles with a particle size of 3 mm, and then ultrasonicated in anhydrous ethanol for 30 minutes at an ultrasonic power of 40 kHz to remove unreacted maleic anhydride to obtain a grafted maleic anhydride composite filler; put the base asphalt into a 155°C oven for heating preparation, then quickly heat it to 180°C, mix 14 parts of the base asphalt with 5 parts of the grafted maleic anhydride composite filler and 2 parts of diatomaceous earth, stir them with a high-speed mixer at 1000rpm for 30min, then add 1 part of 3mm gravel, 0.5 parts of 1mm gravel, 1 part of quicklime powder, and 2.6 parts of lignin fiber, mix and stir homogenously for 30min at a speed of 560rpm and a temperature of 40°C, and obtain a high temperature resistant asphalt mixture after stirring.
[0030] Example 2
[0031] (1) adding basalt fiber with a diameter of 3 mm into a glacial acetic acid solution with a concentration of 1 mol / L, with a solid-liquid ratio of 1:5, and then stirring the solution with a magnetic stirrer for 2 hours at a stirring speed of 120 / rpm; after the stirring, rinsing and filtering with deionized water, and the cycle is repeated twice to clean the basalt fiber; placing the cleaned basalt fiber in an oven for drying, setting the temperature to 50°C, and drying for 8 hours, and obtaining activated basalt fiber after drying;
[0032] (2) Add 16 parts of deionized water to 1 part of chitosan, stir at 120 rpm for 10 min, then add 0.05 parts of acetic acid and 0.4 parts of ethanol, continue to stir for 20 min, then add 1 part of sodium lignin sulfonate and 6.5 parts of activated basalt fiber, stir and react at 80°C for 2 h, the stirring speed is 250 rpm, after the reaction is completed, filter and take the filtrate, wash it twice with deionized water; then mix the washed filtrate with 10 times its volume of deionized water, add nano copper particles, the mass ratio of nano copper to filtrate is 0.35:4, then mix and stir at 120 rpm for 30 min, the temperature is 60°C; after the stirring is completed, filter and take the filtrate, wash it twice with deionized water to wash away the unattached nano copper particles, then place it in a drying oven at a temperature of 60°C for 5 h, and send it to an electron beam irradiation device, react for 12 min at an irradiation energy of 0.7 MeV to obtain a composite filler;
[0033] (3) The rheometer was preheated to 150°C, and then maleic anhydride, dibenzoyl peroxide and composite filler were weighed in a mass ratio of 0.03:5:2. The maleic anhydride, dibenzoyl peroxide and composite filler were mixed, stirred at 60 rpm for 5 min, and then added to the cavity of the rheometer. The mixture was blended at 150°C and 60 rpm for 10 min. After the blending was completed and cooled to room temperature, the blended product was crushed into fine particles with a particle size of 4 mm. The unreacted maleic anhydride was then removed by ultrasonication in anhydrous ethanol for 30 min at an ultrasonic power of 40 kHz. anhydride to obtain a grafted maleic anhydride composite filler; put the base asphalt into a 155°C oven for heating preparation, then quickly heat it to 180°C, mix 14 parts of the base asphalt with 7 parts of the grafted maleic anhydride composite filler and 2 parts of diatomaceous earth, stir with a high-speed mixer at 1000rpm for 30min, then add 1.25 parts of 3mm gravel, 0.75 parts of 1mm gravel, 1.5 parts of quicklime powder, and 2.6 parts of lignin fiber, mix and stir homogenously for 30min at a speed of 560rpm and a temperature of 50°C, and obtain a high-temperature resistant asphalt mixture after stirring.
[0034] Example 3
[0035] (1) adding basalt fiber with a diameter of 3 mm into a glacial acetic acid solution with a concentration of 1 mol / L, with a solid-liquid ratio of 1:5, and then stirring the solution with a magnetic stirrer for 2 hours at a stirring speed of 120 / rpm; after the stirring, rinsing and filtering with deionized water, and the cycle is repeated twice to clean the basalt fiber; placing the cleaned basalt fiber in an oven for drying, setting the temperature to 50°C, and drying for 8 hours, and obtaining activated basalt fiber after drying;
[0036] (2) Add 20 parts of deionized water to 1 part of chitosan, stir at 120 rpm for 10 min, then add 0.06 parts of acetic acid and 0.5 parts of ethanol, continue to stir for 20 min, then add 1.5 parts of sodium lignin sulfonate and 8 parts of activated basalt fiber, stir and react at 80°C for 2 h, the stirring speed is 250 rpm, after the reaction is completed, filter and take the filtrate, wash it twice with deionized water; then mix the washed filtrate with 10 times its volume of deionized water, add nano copper particles, the mass ratio of nano copper to filtrate is 0.5:4, then mix and stir at 120 rpm for 30 min, the temperature is 60°C; after the stirring is completed, filter and take the filtrate, wash it twice with deionized water to wash away the unattached nano copper particles, then place it in a drying oven at a temperature of 60°C for 5 h, and send it to an electron beam irradiation device, react for 15 min at an irradiation energy of 0.7 MeV to obtain a composite filler;
[0037] (3) The rheometer was preheated to 150°C, and then maleic anhydride, dibenzoyl peroxide and composite filler were weighed in a mass ratio of 0.04:5:2. The maleic anhydride, dibenzoyl peroxide and composite filler were mixed, stirred at 60 rpm for 5 minutes, and then added to the cavity of the rheometer. The mixture was blended at 150°C and 60 rpm for 10 minutes. After the blending was completed and cooled to room temperature, the blended product was crushed into fine particles with a particle size of 5 mm, and then ultrasonicated in anhydrous ethanol for 30 minutes at an ultrasonic power of 40 kHz to remove unreacted maleic anhydride to obtain a grafted maleic anhydride composite filler; put the base asphalt into a 155°C oven for heating preparation, then quickly heat it to 180°C, mix 14 parts of the base asphalt with 9 parts of the grafted maleic anhydride composite filler and 2 parts of diatomaceous earth, stir them with a high-speed mixer at 1000rpm for 30min, then add 1.5 parts of 3mm gravel, 1 part of 1mm gravel, 2 parts of quicklime powder, and 2.6 parts of lignin fiber, mix and stir for 30min at a speed of 560rpm and a temperature of 60°C, and obtain a high temperature resistant asphalt mixture after stirring.
[0038] Comparative Example 1
[0039] The difference between Comparative Example 1 and Example 2 is that step (2) is different. Step (2) is changed to: add 16 parts of deionized water to 1 part of chitosan, stir at 120 rpm for 10 minutes, then add 0.05 parts of acetic acid and 0.4 parts of ethanol, continue to stir for 20 minutes, then add 6.5 parts of activated basalt fiber, stir and react at 80°C for 2 hours, the stirring speed is 250 rpm, after the reaction is completed, filter and take the filtrate, wash twice with deionized water; then mix the washed filtrate with The mixture was mixed with deionized water 10 times its volume, nano copper particles were added, the mass ratio of nano copper particles to the filtrate was 0.35:4, and then the mixture was mixed and stirred at a speed of 120 rpm for 30 minutes at a temperature of 60°C; after the stirring, the filtrate was filtered and washed twice with deionized water to remove the unattached nano copper particles, and then placed in a drying oven at a temperature of 60°C for 5 hours, and then sent to an electron beam irradiation device, and reacted for 12 minutes at an irradiation energy of 0.7 MeV to obtain a composite filler; the remaining steps were the same as those in Example 2.
[0040] Comparative Example 2
[0041] The difference between Comparative Example 2 and Example 2 lies in the difference in step (2), where step (2) is changed to: 16 parts of deionized water, 1 part of sodium lignin sulfonate and 6.5 parts of activated basalt fiber are mixed, stirred and reacted at 80°C for 2h, with a stirring speed of 250rpm. After the reaction is completed, the filtrate is filtered and washed twice with deionized water; then the washed filtrate is mixed with deionized water 10 times its volume, nano-copper particles are added, the mass ratio of nano-copper to filtrate is 0.35:4, and then the mixture is mixed and stirred at a speed of 120rpm for 30min at a temperature of 60°C; after the stirring is completed, the filtrate is filtered and washed twice with deionized water to remove the unattached nano-copper particles, and then placed in a drying oven at a temperature of 60°C for 5h, and then sent to an electron beam irradiation device, and reacted for 12min at an irradiation energy of 0.7MeV to obtain a composite filler; the remaining steps are the same as those in Example 2.
[0042] Comparative Example 3
[0043] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: add 16 parts of deionized water to 1 part of chitosan, stir at 120rpm for 10min, then add 0.05 parts of acetic acid and 0.4 parts of ethanol, continue to stir for 20min, then add 1 part of sodium lignin sulfonate and 6.5 parts of activated basalt fiber, stir and react at 80°C for 2h, the stirring speed is 250rpm, after the reaction is completed, filter and take the filtrate, wash it twice with deionized water, then place it in a drying oven at a temperature of 60°C for 5h, and send it to an electron beam irradiation device, react for 12min at an irradiation energy of 0.7MeV to obtain a composite filler; the remaining steps are the same as Example 2.
[0044] Comparative Example 4
[0045] The difference between Comparative Example 4 and Example 2 lies in step (3). Step (3) is changed to: put the matrix asphalt into a 155°C oven for heating preparation, then quickly heat it to 180°C, mix 14 parts of matrix asphalt with 7 parts of composite filler and 2 parts of diatomaceous earth, stir for 30 minutes with a high-speed mixer at 1000rpm, then add 1.25 parts of 3mm gravel, 0.75 parts of 1mm gravel, 1.5 parts of quicklime powder, and 2.6 parts of lignin fiber, mix and stir for 30 minutes at a speed of 560rpm and a temperature of 50°C. After stirring, a high-temperature resistant asphalt mixture is obtained. The remaining steps are the same as those in Example 2.
[0046] Comparative Example 5
[0047] The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: preheat the rheometer to 150°C, then weigh maleic anhydride, dibenzoyl peroxide and composite filler, the mass ratio of maleic anhydride, dibenzoyl peroxide and composite filler is 0.03:5:2, mix them, stir at 60 rpm for 5 minutes, add them to the cavity of the rheometer, blend for 10 minutes at a temperature of 150°C and a speed of 60 rpm; after the blending is completed and cooled to room temperature, the blended product is broken into fine particles with a particle size of 4 mm, and then ultrasonicated in anhydrous ethanol for 30 minutes at an ultrasonic power of 4 0kHz, remove the unreacted maleic anhydride to obtain the grafted maleic anhydride composite filler; put the base asphalt into a 155°C oven for heating preparation, then quickly heat it to 180°C, mix 14 parts of the base asphalt with 7 parts of the grafted maleic anhydride composite filler, stir it with a high-speed mixer at 1000rpm for 30min, then add 1.25 parts of 3mm gravel, 0.75 parts of 1mm gravel, 1.5 parts of quicklime powder, and 2.6 parts of lignin fiber, mix and stir for 30min, the stirring speed is 560rpm, the temperature is 50°C, and after stirring, a high temperature resistant asphalt mixture is obtained; the remaining steps are the same as Example 2.
[0048] Effect example
[0049] Table 1 below shows the performance analysis results of a high temperature resistant asphalt mixture using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0050] Table 1
[0051]
[0052] From the comparison of the wear resistance experimental data of the embodiment and the comparative example, it can be found that the present invention grafts sodium lignin sulfonate and chitosan onto basalt fiber, adsorbs nano-metal particles, and then adds them into nitrile rubber to prepare a composite filler; the hydroxyl groups on the surface of sodium lignin sulfonate, the amino and hydroxyl groups on the surface of chitosan, and the active groups on the surface of the activated basalt fiber react and chemically combine with each other, and the basalt fiber grafted with sodium lignin sulfonate has carbon chains, benzene rings, etc. on the surface, which greatly improves its own dispersibility in rubber, and strengthens the interface force of the basalt fiber as a hard skeleton to support the rubber to form a three-dimensional structure. , so that the combination effect of the two is well improved, thereby comprehensively improving the stability of the composite filler; using the hydroxyl group at the ortho position of the free amino group of chitosan, which has the effect of chelating divalent metal ions, the nano-metal copper particles are adsorbed on the basalt fiber through chelation to form a metal chelate; the nano-metal chelate has a significant effect on inhibiting the cross-linking reaction of the rubber molecular chain caused by free radicals, improving the stability of the rubber's resistance to heat and oxygen aging, and at the same time, because it is attached to the basalt fiber, it is evenly distributed in the composite filler, further improving the high temperature resistance of the composite filler, thereby optimizing the high temperature resistance of the asphalt mixture. Secondly, the present invention grafts maleic anhydride on the composite filler through free radical polymerization, and synergistically modifies asphalt with diatomaceous earth to prepare an asphalt mixture; the addition of diatomaceous earth can react with asphalt to form a stable network structure, and form a stable blend with the composite filler; on this basis, the grafted maleic anhydride not only reduces the problem of excessive viscosity caused by the cross-linking structure, but also further improves the combination effect of the composite filler and other substances in the asphalt mixture due to the introduction of its polar group for functional modification, so as to achieve higher stability.
[0053] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high temperature resistant asphalt mixture, characterized in that: The asphalt mixture is prepared by grafting maleic anhydride with homemade composite filler, adding diatomaceous earth and asphalt, mineral powder and crushed stone as raw materials.
2. A high temperature resistant asphalt mixture according to claim 1, characterized in that: The self-made composite filler is prepared by grafting sodium lignin sulfonate and chitosan onto basalt fiber, absorbing nano-metal particles, and then adding the nano-metal particles into nitrile rubber.
3. A high temperature resistant asphalt mixture according to claim 2, characterized in that: The basalt fiber is activated basalt fiber treated with glacial acetic acid.
4. A method for preparing a high temperature resistant asphalt mixture, characterized in that: The method comprises the following preparation steps: (1) adding basalt fiber to glacial acetic acid solution with a solid-liquid ratio of 1:5, and then stirring the solution with a magnetic stirrer for 2 hours at a stirring speed of 120 / rpm; after the stirring, rinsing and filtering with deionized water, and circulating twice to clean the basalt fiber; placing the cleaned basalt fiber in an oven for drying, setting the temperature to 50°C for 8 hours, and obtaining activated basalt fiber after drying; (2) Add 12-20 parts of deionized water to 1 part of chitosan, stir at 120 rpm for 10 min, then add 0.04-0.06 parts of organic acid and 0.1-0.5 parts of ethanol, continue to stir for 20 min, then add 0.5-1.5 parts of sodium lignin sulfonate and 5-8 parts of activated basalt fiber, stir at 80°C for 2 h, stir at 250 rpm, filter and take out the filtrate after the reaction, wash twice with deionized water; then The filtered material after washing is then mixed with deionized water 10 times its volume, and nano copper particles are added, the mass ratio of nano copper particles to the filtered material is 0.2-0.5:4, and then the mixture is mixed and stirred at a speed of 120 rpm for 30 minutes at a temperature of 60°C; after the stirring is completed, the filtered material is filtered and washed twice with deionized water to remove the unattached nano copper particles, and then placed in a drying oven at a temperature of 60°C for 5 hours, and then sent to an electron beam irradiation device for irradiation reaction for 10-15 minutes to obtain a composite filler; (3) The rheometer is preheated to 150° C., and then a certain amount of maleic anhydride, dibenzoyl peroxide and composite filler are weighed in proportion, mixed, stirred at a speed of 60 rpm for 5 minutes, added to the cavity of the rheometer, and blended for 10 minutes at a temperature of 150° C. and a rotation speed of 60 rpm; after the blending is completed and cooled to room temperature, the blended product is crushed into fine particles with a particle size of 3-5 mm, and then ultrasonicated in anhydrous ethanol for 30 minutes at an ultrasonic power of 40 kHz to remove unreacted maleic anhydride to obtain a grafted maleic anhydride composite filler. The material is prepared by heating the base asphalt in an oven at 155°C, and then rapidly heating it to 180°C, mixing 14 parts of the base asphalt with 5-9 parts of grafted maleic anhydride composite filler and 2 parts of diatomaceous earth, and stirring them with a high-speed mixer at 1000rpm for 30min, and then adding 1-1.5 parts of 3mm crushed stone, 0.5-1 part of 1mm crushed stone, 1-2 parts of ore powder, and 2.6 parts of lignin fiber, and mixing and homogenizing for 30min at a speed of 560rpm and a temperature of 40-60°C. After stirring, a high temperature resistant asphalt mixture is obtained.
5. The method for preparing a high temperature resistant asphalt mixture according to claim 4, characterized in that: The diameter of the basalt fiber in step (1) is 3 mm.
6. The method for preparing a high temperature resistant asphalt mixture according to claim 4, characterized in that: The concentration of the glacial acetic acid solution in step (1) is 1 mol / L.
7. The method for preparing a high temperature resistant asphalt mixture according to claim 4, characterized in that: In the step (2), the organic acid is acetic acid.
8. The method for preparing a high temperature resistant asphalt mixture according to claim 4, characterized in that: The irradiation energy in step (2) is 0.7 MeV.
9. The method for preparing a high temperature resistant asphalt mixture according to claim 4, characterized in that: In the step (3), the mass ratio of maleic anhydride, dibenzoyl peroxide and composite filler is 0.02-0.04:5:
2.
10. The method for preparing a high temperature resistant asphalt mixture according to claim 4, characterized in that: In the step (3), the ore is divided into quicklime powder.
Citation Information
Patent Citations
Durable assistant capable of enhancing ageing resistance of asphalt
CN109135309A
Modified asphalt waterproof adhesive and preparation method thereof
CN117586748A
Chitosan modified asphalt
CN118515984A